A fotografia de folia de reis: do documental à experimentação - Sousa, Karina Alves de (2023)
The folia de reis is a ritual that represents the story of the Three Kings of the East who, following a guiding star, arrived at the birthplace of Jesus. Groups of foliões remember this passage, going from house to house playing, singing and collecting donations to hold a party due to the payment of a promise made by the devotee. This type of celebration takes place in several places in Brazil, presenting similarities and differences around the same religious motif. In this work, folia is the basis of a photographic research developed since 2013. The objective is to experiment with photography through overlapping, using the photo archive built on the folia. The transition from "documentary to experimentation" is a path in which we become aware that, in the vast majority of the works presented, the visuality of folia's photos has a documentary character. The proposal of this doctorate is to produce a theoretical and practical research that explores another way of presenting the photographs of the folia de reis, creating new discourses and ways of showing the party. It is important to question the visualities that are so routine in photographs that seek to document popular festivals, highlighting the passages and crossings that shift the imagery narrative to plural and multidirectional dimensions, typical of the carnival movement of the festival, with its mixture of bodies, objects, sounds and visions. How can the editing techniques applied to the documentary photographs in the researcher's archive reveal, expand and build discourses on the folia de reis? In this context, there is an interesting interweaving between the archived documentary photographs and the vast collection of memories, experiences and knowledge accumulated over the years by the researcher, who has a personal connection with the party as heiress of a lineage of revelers from the Triângulo Mineiro. The objective of the research is to develop a theoretical and practical approach that explores a new way of presenting the photographs of the folia de reis, generating new discourses about this festivity. The aim is to question the visualities and modes of perception present in the folia de reis. For this, we adopted the steps: categorization and classification of the researcher's photographic collection, in order to identify relevant themes, styles and contexts related to folia de reis; elaboration of a poetic production, using the photographic language of superimposition; creation of images that problematize the sociocultural conventions present in the folia de reis groups, challenging and questioning established norms. The justification for this work is based on the need to problematize the documentary images of the folia de reis through editing and overlapping techniques, in order to reveal alternative photographic visualities that show the multiplicity and plurality of sociocultural discourses present in this party. We seek to expand the understanding and reach of the photographs of the folia de reis, going beyond the traditional documentary record, exploring photography as a tool to promote reflections in relation to this cultural manifestation. The research method is composed of bibliographic research on the party, on documentary photography, on overlapping procedures; field research with collection of testimonials and interviews with foliões; procedures with image editing software to compose overlap images; analysis and discussion of visualities obtained in the images resulting from the editing work. The study, of an interdisciplinary nature, is supported by authors of photography, cinema, philosophy and culture, as well as researchers in the field of art, operating mainly with the concepts of image, creation process, cultural miscegenation and baroque